(untitled) (Applied Biological Research, 2016)
The ability of birds to sustain flight and fly in thin air of high altitude is striking evolutionary accomplishments. The extensive anatomical plan of the lung air-sac system of birds is responsible to achieve these accomplishments to which air sacs do play a vital role. A significant difference exists among the birds in these air sacs as seven air sacs in goose (Onuk et al., 2010), nine in rock partridge (Kurtul et al., 2004). Present work was aimed to castigate the occurrence of air sacs in Kuttanad duck and find any variation exists with rest of birds.